2021
DOI: 10.1242/jcs.258655
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear import of BCL11B is mediated by a classical nuclear localization signal and not the Krüppel-like zinc fingers

Abstract: The Krüppel-like transcription factor (KLF) BCL11B is characterized by a wide tissue distribution and crucial functions in key developmental and cellular processes, as well as in various pathologies including cancer and HIV infection. Although the basics of BCL11B activity and relevant interactions with other proteins have been uncovered, how this exclusively nuclear protein localizes to its compartment remained unclear. Here, we demonstrate that unlike other KLFs, BCL11B does not require the C-terminal DNA-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…As a first step to verify whether the BCL11B 213–560 peptide can stimulate the repair of oxidative DNA damage in cells, the peptide was ectopically expressed in RPE1 cells, which express low levels of BCL11B. Since the BCL11B 213–560 peptide does not contain the nuclear localization signal of BCL11B ( 77 ), we added the MYC nuclear localization signal to ensure that the peptide would localize to the nucleus. Measurement of DNA damage by comet assay revealed a decrease in DNA damage in RPE1 cells expressing BCL11B 213–560 as compared to cells harboring the empty vector (Figure 7A , untreated cells).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a first step to verify whether the BCL11B 213–560 peptide can stimulate the repair of oxidative DNA damage in cells, the peptide was ectopically expressed in RPE1 cells, which express low levels of BCL11B. Since the BCL11B 213–560 peptide does not contain the nuclear localization signal of BCL11B ( 77 ), we added the MYC nuclear localization signal to ensure that the peptide would localize to the nucleus. Measurement of DNA damage by comet assay revealed a decrease in DNA damage in RPE1 cells expressing BCL11B 213–560 as compared to cells harboring the empty vector (Figure 7A , untreated cells).…”
Section: Resultsmentioning
confidence: 99%
“…Results from in vitro DNA repair assays showed that BCL11B can stimulate the enzymatic activities of two enzymes of the base excision repair pathway, NTHL1 and Pol β (Figures 4 and 5 ). Moreover, structure-function analysis revealed that the BCL11B region required and sufficient to stimulate DNA repair enzymatic activities, BCL11B 213–560 , does not include the C-terminal zinc fingers that are needed for specific DNA binding nor the N-terminal domains involved in transcriptional regulation and dimerization (Figures 4 , 5 and Supplementary Figure 2 ) ( 60 , 77 ). Importantly, ectopic expression of the BCL11B 213–560 peptide in RPE1 cells led to a reduction of genomic DNA damage and acceleration of DNA repair following treatment with H 2 O 2 (Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Bcl11 TFs can build homo-and heterodimers using an N-terminal C 2 HC zinc-finger domain. This is of functional relevance for the translocation of different Bcl11 isoforms from the cytosol toward the nucleus [26,27]. In humans, there exist at least four relevant isoforms of BCL11A and two of BCL11B, respectively.…”
Section: Bcl11 Transcription Factor Familymentioning
confidence: 94%
“…In contrast, genes close to DARs with increased accessibility in NT-ICM (261 peaks) compared to IVO-ICM were significantly associated with 'negative regulation of cell population proliferation', 'regulation of fibroblast migration', and 'intrinsic apoptotic signaling pathway in response to DNA damage' (Figure 2A). Examples included the inferred cis-elements around BCL11B (a zinc finger TF of the Krüppel-like factor (KLF) family that mediates repression of cell proliferation), 47,48 and XPA (encoding a protein important for DNA damage verification), 49 which showed higher accessibility in NT-ICM than in IVO-ICM (Figures 2D and S2C), suggesting that disturbance of NT-ICM proliferation is related to irregular accessibility of these genes. Further, DARs with higher accessibility in IVO-TE (274 peaks) than NT-TE were associated with 'positive regulation of cell population proliferation', whereas the 'positive regulation of telomere capping' was enriched in NT-TE rather than IVO-TE (326 peaks; Figures 2B and S2D,E).…”
Section: Abnormalities Of Chromatin Accessibility In Icm From Nt Comp...mentioning
confidence: 99%
“…Among the genes related to ICM-AMRs with corrected accessibility, we noticed that BCL11B was not expressed in TEs of either NT-KDM5B or NT-control groups (Figure 6A) and exhibited the most drastically decreased expression in NT-KDM5B ICM compared to NT-control (Figures 5I and S5B). BCL11B inhibits cell proliferation 47,48 and was significantly enriched in multiple GO terms, including 'apoptotic process', 'negative regulation of cell proliferation', and 'keratinocyte development' (Figure 5H). Moreover, based on a previous study, 42 BCL11B transcription is consistently silenced in the early bovine embryos in vivo (Figure 6A), indicating that BCL11B is dispensable for early development.…”
Section: Icm Proliferationmentioning
confidence: 99%